MAKNA GARAM DAN TERANG DUNIA DALAM INJIL MATIUS 5:13-16 DAN IMPLIKASINYA BAGI MASYARAKAT NIAS - Gulo, Syutriska Kardia (GENEVA: JURNAL TEOLOGI DAN MISI, 2023)
Today's world is a world that is faced with endless polemics. Ever since man fell into sin, man has lived in rebellion against God. Because of the chaotic world, the Lord Jesus Himself wants believers to continue to carry out their responsibilities on this earth, namely to be His successors in doing His work in this world, namely to be salt and light for people who do not know God. Seeing the state and condition of the world today which is increasingly degenerating, salt and light should characterize believers, so that through their lives they produce and impact and influence displayed through a consistent attitude to life, integrity, character, and ethics which are the image of Jesus Christ. The purpose of this research is to find out the meaning of salt and light of the world according to the gospel of Matthew 5:13-16 and its implications for Nias society. The research method used in writing this article is literature review and exegesis. Through observations that have been traced, the results of research from the Gospel of Matthew 5: 13-16 show that salt and light have functions that can provide changes wherever they will be.